Error types in Malaysian lower secondary school student writing: a corpus-informed analysis of subject-verb agreement and copula be - Ang, Leng Hong; Tan, Kim Hua; Lye, Guang Yang (Penerbit Universiti Kebangsaan Malaysia, 2020)
The issue of English language proficiency among Malaysian students has always been a subject of ongoing discussion among educators. While English is taught as a second language in primary and secondary schools, many students, especially those from rural areas, have problems using the language correctly. Also, it has been said that students' English language proficiency in most rural contexts takes on the quality of a foreign language rather than a second language. The current study addresses this problem by examining the use of Subject-Verb Agreement and copula be in essays written by 32 Malay lower secondary school students from a rural school in Kedah state, Malaysia. Using corpus-linguistic approach, this study compiled 128 essays and tagged them with online part-of-speech (POS) UCREL CLAWS tagger. This is a novel attempt in integrating Error Analysis (EA) framework with a corpus tagging approach to examine error patterning in learner writing. Using corpus-based techniques, this study identifies and analyses errors associated with SVA and copula be in Malaysian lower secondary school student writing. The findings showed that student writings were riddled with various types of errors, namely misselection, omission, blends, and overinclusion. Based on these findings, this study offers pedagogical suggestions for improving the teaching and learning of the language.